2009
DOI: 10.1002/pssa.200881792
|View full text |Cite
|
Sign up to set email alerts
|

Tin monoxide as an s‐orbital‐based p‐type oxide semiconductor: Electronic structures and TFT application

Abstract: Tin monoxide (SnO) is a stable p-type oxide semiconductor. This paper reports electrical properties, electronic structures, and thin-film transistors (TFTs) of SnO. Epitaxial films were fabricated by pulsed laser deposition. The Hall mobility and the hole density of the epitaxial films were 2.4 cm 2 V −1 s −1 and 2.5 × 10 17 , respectively. X-ray photoelectron spectroscopy (PES) indicated that the closed-shell 5s 2 orbitals of Sn 2+ ions heavily contribute to the hole conduction path in SnO. Top gate type TFTs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

17
191
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 232 publications
(213 citation statements)
references
References 20 publications
17
191
2
1
Order By: Relevance
“…This mechanism is greatly exemplified by tin monoxide (SnO), which shows a high contribution of delocalized Sn 5s states to the VB and of likewise delocalized Sn 5p states to the CB (right-hand side of Figure 1), making the material a promising candidate for transparent applications. 7,11,12 In spite of great improvements in recent years, an even better hole mobility is required for more complex applications. In this direction, recent reports have demonstrated that SnO films deposited in a very Sn-rich environment exhibit a high hole mobility.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This mechanism is greatly exemplified by tin monoxide (SnO), which shows a high contribution of delocalized Sn 5s states to the VB and of likewise delocalized Sn 5p states to the CB (right-hand side of Figure 1), making the material a promising candidate for transparent applications. 7,11,12 In spite of great improvements in recent years, an even better hole mobility is required for more complex applications. In this direction, recent reports have demonstrated that SnO films deposited in a very Sn-rich environment exhibit a high hole mobility.…”
mentioning
confidence: 99%
“…13,24,25 Because the metal states are more spatially spread than the oxygen states, the metallic contribution to the VB renders the good hole mobility of SnO. 9,11,12 Therefore, an increase in the metallic contributions to the VB edge is expected to further enhance the hole mobility. Figure 4 presents the calculated electronic structures of SnO with V Sn , O i , V O , and Sn i defects, focusing on the region from À2 to 2 eV.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5,7 However, SnO TFTs generally operate in the depletion mode and have a high off-state current owing to the high hole concentration and the low resistivity of the SnO films. 7−11 It is reported that the conductivity in SnO is related to tin vacancy and controllable also by impurity doping.…”
mentioning
confidence: 99%
“…Tin oxide (SnO) applied for p-type semiconductor has a large electronic conductivity due to 5s orbital structure of Sn in valence band maximum. SnO has been attracting immense attention as transparent devices such as thin films transistor [3] . When the zinc tin oxide (ZTO) was synthesized using Zn and Sn, it showed the reduction of significant oxygen vacancy [4] .…”
Section: Introductionmentioning
confidence: 99%